Evaluation of Cells Cracks Impact on PV Module’s Performance - Christine Abdel Nour; Julien Dupuis; Paul Lefillastre; Axel Becker (SiliconPV Conference Proceedings)
This work aims to perform an assessment of cell cracks impact on PV module’s performances. Cracks can occur during transportation, severe weather conditions such as hailstorms [1], poor installation practices and manufacturing [2]. Even with multiwire interconnection technologies, the impact of such defects can affect PV module’s performances as well as the energy yield and lifetime of a photovoltaic installation [3]. Moreover, cracks will leave the silicon edge unpassivated with a risk of being more sensitive to external stresses, especially on highly efficient technologies like TOPCon. The main objective of this work is studying the cracks impact on new module’s technology performance to quantify its impact on the production yield and forecast power plant performance. A laboratory testing sequence was performed on two different Glass/backsheet PV technologies: PERC and TOPCon. First, a cracking procedure was conducted to generate several cracks patterns on two batches of PV modules similar to the patterns observed on powerplants sites. An electrical characterization was then performed to carry out a first evaluation of power losses after the cracks. Moreover, several accelerated aging sequences were conducted on the cracked and reference modules to quantify the average losses after each accelerated aging test.